Effects of dietary supplementation of leaves and whole plant of Andrographis paniculata on rumen fermentation, fatty acid composition and microbiota in goats - Yusuf, Aisha L. (BioMed Central, 2017)
Background: The nature and amount of dietary medicinal plants are known to influence rumen fermentation and nutrient digestibility in ruminants. Nonetheless, changes in nutrient digestibility and rumen metabolism in response to dietary Andrographis paniculata (AP) in goats are unknown. This study examined the effects of dietary supplementation of leaves and whole plant of AP on nutrient digestibility, rumen fermentation, fatty acids and rumen microbial population in goats. Twenty-four Boer crossbred bucks (4 months old; average body weight of 20.18 ± 0.19 kg) were randomly assigned to three dietary groups of eight goats each. The dietary treatments included a control diet (Basal diet without additive), basal diet +1.5% (w/w) Andrographis paniculata leaf powder (APL) and basal diet +1.5% (w/w) Andrographis paniculata whole plant powder (APW). The trial lasted 100 d following 14 d of adjustment. Results: The rumen pH and concentration of propionate were greater (P < 0.05) in goats fed the APL and APW diets than those fed the control diet. The concentrations of ammonia nitrogen and acetate were greater (P < 0.05) in the control goats than the APL and APW goats. The digestibilities of crude protein, dry matter, acid detergent fibre and neutral detergent fibre were greater (P < 0.05) in the APL and APW goats compared to the control goats. Dietary APL and APW decreased (P < 0.05) the ruminal concentration of C18:0 and increased (P < 0.05) the ruminal concentration of C18:2n-6 and C18:3n-3. The APL goats had greater (P < 0.05) ruminal concentration of C18:1 trans-11 and CLA cis-9 trans-11 than the APW and control goats. Dietary treatments had no significant effect on the population of protozoa and methanogens in the rumen of goats. The ruminal populations of Ruminococcus albus, Ruminococcus flavefaciens and Fibrobacter succinogenes were greater (P < 0.05) in the APL and APW goats than the control goats. Conclusion: Dietary supplementation of leaves and whole plant of Andrographis paniculata can be used to manipulate rumen metabolism for improved nutrient digestibility in goats.